Exemplary Youth Leadership Series: Enable Others to Act - Megan Stein (EDIS)
This publication series is designed to outline strategies and experiences to expose youth to and engage them with leadership concepts. In this new 2-page publication of the UF/IFAS Department of Agricultural Education and Communication, students will try on aspects of the fourth practice of exemplary leaders: enable others to act. Two quick, low-cost activities are included for implementation with youth. These activities are best suited for students ages 10–18. However, modifications are included for each of the activities to allow for different group sizes, ages, and abilities of the youth participating. Written by Megan Stein. https://edis.ifas.ufl.edu/wc369